2004
DOI: 10.1007/s00213-003-1692-7
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged nicotine dependence associated with extended access to nicotine self-administration in rats

Abstract: There was no escalation in nicotine intake with extended access conditions, unlike cocaine self-administration. Nevertheless, daily nicotine self-administration seven days per week, for either 1 or 6 h per day, was sufficient to induce long-lasting adaptations in nicotinic acetylcholine receptor activity reflected in spontaneous and antagonist-precipitated somatic signs of withdrawal, possibly reflecting aspects of nicotine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
82
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 40 publications
18
82
2
Order By: Relevance
“…Thus, it is possible that access to nicotine self-administration for durations longer than the 20 days reported here may induce further adaptations in brain reward systems similar to those observed in rats treated with nicotine via mini-pumps, and in cocaine self-administering rats. Nevertheless, repeated 1 or 6 h daily access to nicotine self-administration was recently shown to induce 'physical' dependence on nicotine, such that a spontaneous somatic withdrawal syndrome was observed 23 h after cessation of nicotine intake (Paterson and Markou, 2004). Thus, although somatic signs of spontaneous withdrawal were not investigated in the present study, it is likely that 'physical' dependence on nicotine developed in parallel with the reward hypersensitivity reported here.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, it is possible that access to nicotine self-administration for durations longer than the 20 days reported here may induce further adaptations in brain reward systems similar to those observed in rats treated with nicotine via mini-pumps, and in cocaine self-administering rats. Nevertheless, repeated 1 or 6 h daily access to nicotine self-administration was recently shown to induce 'physical' dependence on nicotine, such that a spontaneous somatic withdrawal syndrome was observed 23 h after cessation of nicotine intake (Paterson and Markou, 2004). Thus, although somatic signs of spontaneous withdrawal were not investigated in the present study, it is likely that 'physical' dependence on nicotine developed in parallel with the reward hypersensitivity reported here.…”
Section: Discussionmentioning
confidence: 64%
“…These rats also display a compensatory increase in nicotine IVSA when the dose is lowered (0.03 to 0.003 mg/kg) and a decrease in nicotine-seeking behavior when nicotine is replaced with saline. Moreover, male rats display nicotine IVSA in extended access models (6 -23 h) using low nicotine doses (0.00375 mg/kg/injection), and the level of nicotine intake approximates that of human smokers (Valentine et al, 1997;Paterson and Markou, 2004;Kenny and Markou, 2006). The 23-h access model of nicotine IVSA seems to be sensitive to genetic differences, since nicotine intake is more quickly acquired and persistently maintained in Lewis versus Holtzman and Fisher strains of male rats (Brower et al, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…All drugs were dissolved in 0.9% sterile saline, and mecamylamine was administered in a volume of 1 ml/kg. The drug doses were selected based on previous work in our laboratory (Watkins et al, 1999;Paterson and Markou, 2004) and that of others using extended access to nicotine IVSA (Valentine et al, 1997;Fu et al, 2001;Lesage et al, 2002Lesage et al, , 2003.…”
Section: Drugsmentioning
confidence: 99%
“…The escalation of drug intake with prolonged or extended access is not exclusive for cocaine and ethanol. In both operant self-administration and oral ingestion setups, escalation of drug intake has been observed for other drugs of abuse, including the psychostimulants methamphetamine, amphetamine and methylphenidate (e.g., Kitamura et al, 2006), the opiates heroin and etonitazene (Wolffgramm and Heyne, 1995;Heyne, 1996;Ahmed et al, 2000) but, remarkably, much less so for nicotine (Paterson and Markou, 2004;Kenny and Markou, 2006). Consistent with the notion that escalation of drug intake is an important step in the development of compulsive drug use, it has been shown that, after escalated cocaine or alcohol self-administration, other behavioral characteristics of addictive behavior can also be observed.…”
Section: Escalation Of Drug Usementioning
confidence: 99%